EVOLUTION OF DIGITAL CUSTOMS REGULATIONS IN INTERNATIONAL TRADE (MEXICO) - Contreras, Porfirio Tamayo; Mosqueda, Rafael Espinosa; Rangel, Héctor Fabian Gutiérrez; Rodríguez, Ángel Gutiérrez (Editora Impacto Científico, 2025)
Digital transformation in customs has redefined international trade by streamlining procedures, reducing costs, and improving transparency. This article examines the evolution of digital customs regulations in Mexico, from the adoption of electronic systems (e.g., Single Window) to the most recent reforms. It takes a mixed legal, economic, and technological approach: analyzing legal changes such as the creation of the National Customs Agency of Mexico (ANAM) and Customs Law reforms, the economic benefits in trade facilitation, and technological innovations (digital platforms, big data, blockchain, etc.). Furthermore, a structural equation model is proposed to evaluate relationships between the regulatory framework, customs technology adoption, and trade performance, presenting hypothetical results and discussing implications for the future. DOI: https://doi.org/10.56238/edimpacto2025.084-018